Effect of Crop Rotations in Reducing the Nutrient Loss in Alluvial Tracts of Uttar Pradesh - Goel, K.N.; Khanna, M.L. (Journal of Soil and Water Conservation, 2022)
Maintenance of a favourable equilibrium between losses and gains of nutrients is the basis of good modern agriculture. Barrous and Kilmer (1963) have described the removal of elements by by erosion to be, non-selective as all forms of nutrients are lost by erosion and to be selective in the sense that organic matter and finer particles of soil relatively high in plant nutrients are more vulnerable to erosion.